Enriched environment treatment promotes neural functional recovery together with microglia polarization and remyelination after cerebral ischemia in rats - Yu Han; Xinya Shen; Zhenkun Gao; Pingping Han; Xia Bi (Brain Research Bulletin, 2024)
Background: Microglia activation and oligodendrocyte maturation are critical for remyelination after cerebral ischemia. Studies have shown that enriched environment (EE) can effectively alleviate stroke-induced neurological deficits. However, little is known about the mechanism associated with glial cells underlying the neuroprotection of EE. Therefore, this study focuses on investigating the effect of EE on activated microglia polarization as well as oligodendrogenesis in the progress of remyelination following cerebral ischemia. Methods: The ischemia/reperfusion (I/R) injury model was established by middle cerebral artery occlusion (MCAO) in rats. Animals executed 4 weeks of environmental intervention after performing MCAO or sham surgery and were divided into sham, MCAO, and MCAO+EE groups. Cognitive function, myelin damage, microglia activation and polarization, inflammation, oligodendrogenesis, remyelination, and protein expression of the PI3K/AKT/GSK3β signaling pathway were determined. Results: The staining of NeuN indicated that the infarct size of MCAO rats was decreased under EE. EE intervention improved animal performance in the Morris water maze test and novel object recognition test, promoting the recovery of cognitive function after I/R injury. EE treatment alleviated myelin damage in MCAO rats, as evidenced by the lower fluorescence intensity ratio of SMI-32/MBP in MCAO+EE group. EE increased the fluorescence intensity ratio of NG2+/Ki67+/Olig2+, MBP, and MOG, enhancing the proliferation and differentiation of OPCs and oligodendrogenesis after MCAO. In terms of remyelination, more myelinated axons and lower G/ratio were detected in MCAO+EE rats compared with MCAO group. Moreover, EE treatment decreased the number of Iba1+/CD86+ M1 microglia, increased the number of Iba1+/CD206+ M2 microglia, and suppressed the inflammation response after I/R injury, which could be attributed to the augmented expression of PI3K/AKT/GSK3β axis. Conclusion: EE improved long‑term recovery of cognitive function after cerebral I/R injury, at least in part by promoting M2 microglia transformation through activation of the PI3K/AKT/GSK3β signaling pathway, inhibiting inflammation to provide a favorable microenvironment for oligodendrocyte maturation and remyelination. The effect of the EE on myelin and inflammation could account for the neuroprotection provided by EE.